Kodeks upravljanja javnih delniških družb - Mlakar, Nataša (Podjetje in delo, 2014)
The Corporate Governance Code contains autonomous rules reflecting standards and recommended practices of good corporate governance and sets concrete guidelines for the effective company management and corporate governance. The author discusses and compares the Slovenian Code of Corporate Governance, adopted in December 2009, and The UK Corporate Governance Code, adopted in September 2012. While according to the UK corporate law only one-tier management system of corporate governance is possible, shareholders in Slovenia can autonomously choose either a two-tier management system with management and supervisory board or one-tier management system with the board of directors. Beside system of corporate governance, essential difference between the codes of corporate governance also refers to the participation of employees and their role in the management of joint stock companies. Also some other, equally important, similarities and differences between the two codes are presented.
Keywords: delniške družbe; kodeksi; management; soupravljanje; upravljanje; vodenje; zaposleni